Demography of Transgender, Nonbinary and Gender Minority Populations - Baumle, Amanda K.; Nordmarken, Sonny (Springer International Publishing, 2022)
.Part 1: Conceptualization and Measurement -- Chapter 1. Barriers to a Comprehensive Demography of Transgender and Nonbinary Youth in the United States, Karnoski -- Chapter 2. Capturing Trans: Conceptualization, Measurement, and Shifts, Compton -- Chapter 3. Hidden (and not so hidden) messaging in top utilized U.S. social surveys: the persistence of heteronormative ideology and the gender binary, Tabler et. al -- Chapter 4. Gender as a Journey: Rethinking the Narratives around Identity Formation for Non-binary Individuals, Vega et. al -- Part 2: Population Characteristics and Public Attitudes -- Chapter 5. Trans mobility across borders: An intersectional account of trans diaspora in migration studies, Jorquera et. al -- Chapter 6.Demographic and Socioeconomic Analyses of the Transgender and Cisgender Populations, Poston et. al -- Chapter 7. Attitudes Toward Rights and Privileges for Transgender People: Evidence from a National Survey ExperimentDoan et. al -- Chapter 8.Work, Inequality, and the Transgender Population, Baumle -- Part 3: Health and Healthcare Disparities -- Chapter 9. Health and Healthcare Utilization among TGNC Black and Hispanic/Latinx Adolescents, Carter et. al -- Chapter 10. Protective and Restrictive Transgender-Specific U.S. State Policies and Mental and Physical Health Among Transgender and Other Gender Diverse People, Goldenberg and Stephenson -- Chapter 11. Transgender Health in the American South: Attitudes, Behaviors, Experiences, & Outcomes, Austin et. al -- Chapter 12. Correlates of Suicide Risk among Binary and Non-Binary Transgender Young Adults, Wilkinson et. al -- Conclusion: Current knowledge and future needed research.